Role of MRI to confirm healing in complex high cryptoglandular anal fistulas: long‐term follow‐up of 151 cases. (27th May 2021) - Garg, Pankaj; Yagnik, Vipul D.; Kaur, Baljit; Menon, Geetha R.; Dawka, Sushil
Abstract: Aim: Complex fistula‐in‐ano can recur even after complete clinical healing has occurred. 'Radiological healing' of fistula on MRI correlates well with long‐term healing rates but no study has yet objectively quantified this. The aim of this study was to assess the accuracy of anal fistula healing as documented on MRI and to correlate it with long‐term healing as evidenced on long‐term follow‐up. Methods: Patients with clinically healed anal fistulas who also had radiological healing checked by postoperative MRI were included in the study. Results: Three hundred and twenty‐five patients operated for high complex fistula‐in‐ano were followed up for 14–68 months (median 38 months). Postoperative MRI was done to assess radiological healing of the fistula in 151 patients, and they were included in the study. The mean age was 39.4 ± 10.5 years (116 men). Five patients were lost to follow‐up. The fistulas did not heal radiologically (on MRI) in 20 patients and recurred in all these patients. The fistulas healed radiologically (on MRI) in 126 patients. On long‐term follow‐up, 124/126 patients remained healed while 2/126 had a recurrence. In the first patient, the fistula recurred 40 months after complete radiological healing. In the second patient, the fistula recurred 10 months after complete radiological healing but pus from the fistula tested positive for tuberculosis (by real‐time polymerase chain reaction) and he was excluded from the analysis. Thus, there was only one (1/125) recurrence on long‐term follow‐up. Conclusions: Radiological healing on MRI correlates well with long‐term healing in complex fistula‐in‐ano.